3 + 3 x 3 - 3 + 3 =? What is the right answer and how? (1) 18 (2) 12 (3) 03 (4) 06

Answer: (2) 12

We can solve the above mentioned problem by using BODMAS rule. According to BODMAS rule, if an expression contains brackets ((), {}, []) we have first to solve or simplify the bracket followed by ‘order’ (that means powers and roots, etc.), then division, multiplication, addition and subtraction from left to right.

3 + 3 x 3 – 3 + 3

First perform multiplication

3 x 3 = 9

the equation becomes

3 + 9 – 3 + 3

Addition of the numbers(3 + 9)

3 + 9 = 12

equation becomes

12 – 3 + 3

⇒ 12 + 3 = 15

⇒ 15 – 3 = 12

Was this answer helpful?

  
   

4 (11)

Upvote (18)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question